“Harmoni” dalam profesionalisme sebagai pustakawan tunggal: Studi kasus Perpustakaan Teknik Pertambangan Institut Teknologi Bandung - Resti Andriani (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2017)
One Person Librarian is a librarian who manages libraries in an institution / institution alone. This phenomenon has become increasingly common in libraries majoring in / faculty of universities apply this model. This can be due to a lack of professional librarians and cost efficiency. The author is a librarian who manages library majors alone, or often called One Person Librarian. Activities undertaken are collection development, library material processing, service and other library administration activities. In the course of time must sometimes feel saturated, but must always be remembered the motto of ITB is "Harmonia in Progressio", from the translation of the word "HARMONI" the author tries to apply it as One Person Librarian in order to have a high professionalism and service to the user increasing..